PENGARUH MODEL PEMBELAJARAN KOOPERATIF TPS (THINK PAIR SHARE) TERHADAP KETERAMPILAN MENULIS KARANGAN SEDERHANA PADA SISWA KELAS V SDN PELA - Fatmah; Zulkifli; Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of implementing the Think Pair Share (TPS) cooperative learning model on elementary school students' learning outcomes. The background of this study is based on the importance of implementing learning strategies that can increase students' active involvement in the learning process so that learning outcomes can be more optimal. The research method used was a quasi-experimental design with a non-equivalent control group design. The research subjects consisted of two classes, namely the experimental class given treatment using the TPS learning model and the control class using conventional learning. The results of data analysis showed that the initial abilities (pretest) of students in the experimental class and the control class were relatively the same, with an average score of 61.50 in the experimental class and 60.75 in the control class. The t-test on the pretest scores showed no significant difference between the two classes (sig. = 0.749 > 0.05), so it can be concluded that students' initial abilities were in a balanced condition. After being given treatment, the posttest results showed a significant difference. The experimental class obtained an average score of 81.20, higher than the control class with an average of 71.40. The t-test results also confirmed a significant difference (t count = 4.512 > t table = 2.024; sig. = 0.000). Based on these findings, it can be concluded that the implementation of the Think Pair Share (TPS) cooperative learning model has a positive and significant effect on student learning outcomes. This model is able to increase student interaction, cooperation, and understanding, making it more effective than conventional learning.